The Effect of School Environment and Extrinsic Motivation on Teacher Performance - Octoviani, Eka; Ahmad, Syarwani; Kesumawati, Nila (Journal of Social Work and Science Education, 2022)
The school environment is a physical and non-physical situation that occurs within the purview of the school. The school atmosphere is assisting instructors in developing motivation. As a result, the purpose of this study was to prove hypotheses regarding the effect of the school environment and extrinsic motivation on teacher performance. The quantitative descriptive approach was employed in the implementation of this research. The population is 125 persons, with 30 people serving as a trial sample and 95 people serving as the study's main sample. Data was collected through questionnaires, observations, and documentation approaches. In this study, data were analyzed using inferential statistics such as simple correlation tests, multiple correlation tests, t-tests, and f-tests Ogan Komering Ilir Regency, Jejawi District. According to the findings of the study, the school environment and extrinsic motivation have an impact on the performance of State Junior High School teachers in Jejawi District, Ogan Komering Ilir Regency, both partially and concurrently.